THE INFLUENCE OF MOTIVATION AND COMPENSATION ON EMPLOYEE TURNOVER INTENTION AT PT AJI - Topan dewa perdana; Ika Korika Swasti (PT Larva Wijaya Penerbit, 2024)
Abstract: This study aims to determine the influence of motivation and compensation on employee turnover intention at PT AJI. The research employs a quantitative method. The sampling was conducted using the probability sampling method with a simple random sampling technique, resulting in a sample of 57 employees from PT AJI. Data collection was carried out using questionnaires distributed to the employees. The study's variables include the independent variables motivation (X1) and compensation (X2), as well as the dependent variable turnover intention (Y). The analysis tool used in this research is the Partial Least Squares (PLS) model. The results indicate that motivation and compensation collectively have a negative and significant effect on employee turnover intention at PT AJI. Keywords: Motivation, Compensation, Turnover Intention, Employees.